2020
DOI: 10.1111/1753-0407.13106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inspiratory muscle training on respiratory muscle strength and functional capacity in patients with type 2 diabetes mellitus: A randomized clinical trial

Abstract: Background Type 2 diabetes mellitus (T2DM) is usually associated with respiratory manifestations including inspiratory muscle weakness which affects exercise capacity. The present study aimed to determine the effect of inspiratory muscle training (IMT) on inspiratory muscle strength and exercise capacity in patients with Type 2 diabetes mellitus (T2DM). Methods This was a randomized controlled trial in patients with type 2 diabetes mellitus with no previous cardiopulmonary or neuromuscular diseases. Patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In the protocols, IMT loads ranged between 30% and 75% of the maximum inspiratory pressure (MIP) for at least eight weeks, with a frequency between three and seven times a week ( Table 3 ). Considering six RCTs, three showed an increase in MIP and did not assess muscle endurance [ 13 , 19 , 24 ] . One showed an increase in MIP and endurance [ 25 ] and one obtained an increase only in muscular endurance, with no difference in MIP after the protocol [ 26 ] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the protocols, IMT loads ranged between 30% and 75% of the maximum inspiratory pressure (MIP) for at least eight weeks, with a frequency between three and seven times a week ( Table 3 ). Considering six RCTs, three showed an increase in MIP and did not assess muscle endurance [ 13 , 19 , 24 ] . One showed an increase in MIP and endurance [ 25 ] and one obtained an increase only in muscular endurance, with no difference in MIP after the protocol [ 26 ] .…”
Section: Resultsmentioning
confidence: 99%
“…In one study, there was a reduction in glycemic levels in eight weeks of protocol [ 26 ] . Two studies demonstrated that IMT increased functional capacity, which was assessed by the six-minute walk test (6WT) [ 24 ] , and VO2max, assessed by the cardiopulmonary exercise test [ 13 ] . They were considered high-quality (> 7 points) and moderate-quality (6 or 5 points) studies, respectively ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this, some safe and viable assessment tools can be used, mainly in T2DM, such as the six-minute walk test and the step test. As important as aerobic exercise is strength training, which can be based on 1-repetition maximum assessment, as demonstrated by studies with individuals with T1DM and T2DM ( 62 64 ).…”
Section: Introductionmentioning
confidence: 99%